Decision of the Jayapura City Muslim Community in Paying Zakat, Infaq and Alms (Proceeding of International Conference on Islamic Economics, Islamic Banking, Zakah and Waqf, 2023)
This study aims to investigate and analyze the optimization of zakat infaq and alms collection to reach its potential. Nationally, the city of Jayapura, zakat literacy and income is one of the determining factors in people's decisions in paying zakat, infaq and alms. This study uses quantitative methods with multiple linear regression analysis using SPSS.25. The research population is all Muslim communities in Jayapura City. Distribution of questionnaires to 150 respondents who have or have not paid zakat, infaq and alms to zakat institutions in Jayapura City. The results showed that zakat literacy and income variables can influence the decisions of the Jayapura City Muslim community in paying zakat, infaq and alms, thus zakat literacy and one's income are able to explain how to maximize the potential of zakat infaq and alms in Jayapura city. These findings recommend that institutions and local governments continue to improve understanding and provide public information regarding zakat by holding zakat literacy socialization to the Muslim community in Jayapura city through further use of digitalization, local governments are encouraged to continue to pay special attention to UMKM so that they can increase the income of local communities.